(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to assess the concentration level of heavy metals in water of the Turag river during the months from January to March, 2014. The level of Pb, Cd, Cr, Cu, Hg and Fe ranged from 0.002-0.005 ppm, BDL (Below Detection Level)-0.03 ppm, 0.007-0.024 ppm, 0.03-0.15 ppm, BDL (Below Detection Level)-0.00024 and 0.78-6.33 ppm, respectively. The concentration level of heavy metals in water did not exceed the permissible limit except Fe. This result was obtained because of river water is always flowing and metals cannot be accumulated in flowing water. For this reason a little amount of analyzed heavy metals were traced in water samples. But heavy metals have toxic properties, leading to adverse effects on human and ecosystem health even in small doses. So, the Turag river water is not safe for using different purposes and steps should be undertaken to improve the water quality of the river. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22221 J. Environ. Sci. & Natural Resources, 7(2): 133-136 2014